Incidence of Cisplatin Ototoxicity in Head and Neck Cancer Patients. (2nd September 2014) - Greene, Joshua B.; Standring, Robert T.; Hall, Francis T.; Siddiqui, Farzan; Ahsan, Syed F.
Abstract : Objectives: Elucidate the incidence of cisplatin‐induced ototoxicity in patients treated for head and neck cancer. Methods: This was an institutional review board approved retrospective study of patients treated with cisplatin for cancer at a tertiary referral hospital. The charts of patients of any age that had undergone cisplatin therapy from 1995 to the present were reviewed. We then narrowed this group down to those who had a diagnosis of cancer of the head and neck (hypopharyngeal, laryngeal, nasopharyngeal, oropharyngeal, scalp/face skin cancer, temporal, thyroid) and had pre‐ and posttreatment audiologic testing. Results: There were 1565 patients that had undergone therapy with cisplatin from 1995 to 2014. Of those, 203 patients had pre‐ and posttreament audiologic testing. Twenty patients had diagnosis of cancer involving the head and neck. The cochlear radiation doses were also collected from these patients. Preliminary results demonstrate that patients with head and neck cancer that were treated with cisplatin and had a sizable cochlear radiation dose had significantly more permanent hearing loss following treatment. Conclusions: The incidence of cisplatin induced ototoxicity was significantly more prevalent in head and neck cancer patients. These patients should be thoroughly screened and protective precautions should be taken to limit ototoxicity in this population.